The sedation efficacy of different doses of remimazolam in elderly patients with regional nerve block anaesthesia - Wan-jun Yang; Zhi-long Geng; Zheng-ze Chen; Chao-yuan Cui; Zi-wei Tian; Xi-lin Guo; Ya-nan Zhang; Lu Wang; Rui Huo; Chen-wei Ma; Yuan-yuan Gao (European Journal of Medical Research)
Abstract Background Remimazolam is a benzodiazepine sedative that is indicated for induction and maintenance during general anaesthesia. Remimazolam is also used for sedation in outpatient surgery; however, most reports have focused on nonelderly patients, whereas only a few studies have reported the use of remimazolam for elderly patients when receiving regional nerve block anaesthesia. Aim The aim of this study was to evaluate the effects of different doses of remimazolam in elderly patients when specifically related to regional nerve block anaesthesia. Methods This study was conducted at a university hospital between February 2022 and March 2023. We included 80 patients aged 65 years or older under regional nerve block anaesthesia. After the effects of anaesthesia were determined, patients were intravenously administered different doses of the test drug, i.e. 4, 4.5, 5, 5.5, or 6 mg, which were named the R1, R2, R3, R4, and R5 groups, respectively. The primary outcome was the loss of consciousness time. The secondary outcomes included the maintenance time and the number of assisted ventilators needed. The exceptional response of patients in terms of loss of consciousness maintenance time, the mean arterial pressure (MAP), heart rate (HR), respiratory rate (RR), SpO2, and modified observers assessment of alertness/sedation (MOAA/S) scores were recorded at baseline (T0), 3 min after the injection of the test drug (T1), 6 min after the injection of the test drug (T2), 9 min after the injection of the test drug (T3), 12 min after the injection of the test drug (T4), 15 min after the injection of the test drug (T5), 18 min after the injection of the test drug (T6), 21 min after the injection of the test drug (T7), and 24 min after the injection of the test drug (T8). Results We included 80 patients according to the inclusion and exclusion criteria, with 16 patients in each group. There were no significant differences in sex, age, and BMI amongst the 5 groups. The loss of consciousness time was significantly greater in the R2 group than in the R3, R4, and R5 groups (p < 0.001), and the loss of consciousness maintenance time was significantly greater in the R5 group than in the R3 group (p < 0.05). The MAP was significantly lower in the R2 and R5 groups than in the R1 group at T4 (p = 0.004) and significantly lower in the R5 group than in the R1 group at T5 (p = 0.007). The HR was significantly lower in the R5 group than in the R3 group at T3 (p = 0.004) and T4 (p = 0.007). The RR was significantly lower in the R5 group than in the R4 group at T4 (p = 0.049) and significantly greater in the R4 group than in the R2 group at T5 (p = 0.024) and T6 (p = 0.020). The RR was significantly lower in the R5 group than in the R1, R3 and R4 groups at T7 (p = 0.001). The RR was significantly greater in the R1 group than in the R2 and R5 groups at T8 (p = 0.001). The RR was significantly greater in the R4 group than in the R2 group at T8 (p = 0.001). SpO2 was significantly lower in the R3 group than in the R1 group at T3 (p = 0.003) and significantly lower in the R3 group than in the R1 and R5 groups at T4 (p = 0.002), T5 (p = 0.001), T6 (p = 0.000), and T7 (p = 0.000). The MOAA/S scores were significantly lower in the R4 and R5 groups than in the R1 and R2 groups at T1 (p = 0.000), significantly lower in the R5 group than in the R1 and R3 groups at T2 (p = 0.004), and significantly lower in the R5 group than in the R1 group at T3 (p = 0.036). Conclusion The results indicated that doses of 5–5.5 mg remimazolam are more suitable for sedation in elderly patients, and the loss of consciousness time and depth of sedation differed according to the remimazolam dosage. Doses of 5–5.5 mg remimazolam were associated with adequate levels of sedation in elderly patients and with a decreased risk of complications, whilst haemodynamic fluctuations occurred approximately 12–15 min after the administration of remimazolam.